The study of reduced susceptibility of methicillin resistant Staphylococcus aureus to various antibiotics with special reference to glycopeptides in a tertiary care hospital in central India - Kale, Swati S.; Patil, Ashwini (International Journal Of Community Medicine And Public Health, 2019)
Background: Staphylococcus aureus has emerged over the past several decades as a leading cause of hospital-associated and community acquired infections. Methicillin resistant S. aureus (MRSA), which are often resistant to several classes of antibiotics, is the most common cause of nosocomial infections and pose a great threat to the world. Vancomycin is regarded as the first-line drug for treatment of MRSA but resistance to this drug is being reported now a day. Methods: It was carried out for a period between January 2014 to June 2017 in the microbiology diagnostic laboratory. MRSA detection was performed by cefoxitin disk diffusion method. Screening for the vancomycin intermediate and the vancomycin resistant S. aureus (VISA and VRSA respectively) was carried out by using vancomycin screen. MIC (minimum inhibitory concentration) of vancomycin was tested by agar dilution method and E strip on all MRSA isolates. Results: A total of 287 S. aureus clinical isolates were included in the study. All MRSA were inoculated on vancomycin screen agar. Visible growth was present in 8 isolates. Five (3.73%) MRSA isolates with MIC of 4 were termed VISA (vancomycin intermediate S. aureus) by agar dilution method. Six isolates had the MIC of 4 and were termed as VISA. Conclusions: As disc diffusion method is not recommended by CLSI for S. aureus, vancomycin screen agar and MIC determination by either of the methods viz. agar dilution or E test can be used.